REFLECTIONS ON THE PRACTICE OF EDUCATION IN INITIAL SERIES AND INFANTILE AGGRESSIVITY (Fiep Bulletin - online, 2013)
Has the first results of a study involving the analysis of conceptions of childhood and the stage of the practice of disciplines of Physical Education in a class 1st series, which belongs to a school network city of Pelotas/RS/Brazil. The goal of the study was to reflect as the use of some content and objectives of critical approach superadora advocated by book Coletivo de Autores (1992), could help to reduce aggression and improve socializing between pupils of this class, who belong to a natural reality in our society. As a preliminary conclusion of the study is can indicate that the methodology used in classes contributed to greater sociability class.
Keywords: Physical Education; Childhood and Sociability